An Effectiveness of Using Inquiry-Based Learning Models on Student Learning Outcomes: Meta Analysis - Putri, Yuzia Eka (AI Society & STMIK Indonesia, 2024)
This research analyzes the effectiveness of using an inquiry-based learning model on student learning outcomes. The inquiry learning model has five important principles that must be considered in the learning process, namely oriented towards intellectual development, the principle of interaction, the principle of asking, the principle of learning to think and the principle of openness. The data in this research consists of 21 articles. Data obtained from research results that have been published in national and international journals sourced from Google Schoolar, and SINTA with a publication period of 2018-2023. The requirements for selecting articles are 1) the article has research data 2) the research must be experimental or quasi-experimental 3) the article has supporting data to calculate the effect size. Data analysis using the JASP application. The results of data analysis show that the average effect size value is in the high category, namely 1.60. This shows that the inquiry learning model is effective in improving student learning outcomes